Modulation of Legume Defense Signaling Pathways by Native and Non-native Pea Aphid Clones - Sanchez-Arcos, Carlos; Reichelt, Michael; Gershenzon, Jonathan; Kunert, Grit (Frontiers in Plant Science, 2016)
The pea aphid (Acyrthosiphon pisum) is a complex of at least 15 genetically different host races that are native to specific legume plants, but can all develop on the universal host plant Vicia faba. Despite much research it is still unclear why pea aphid host races (biotypes) are able to colonize their native hosts while other host races are not. All aphids penetrate the plant and salivate into plant cells when they test plant suitability. Thus plants might react differently to the various pea aphid host races. To find out whether legume species vary in their defense responses to different pea aphid host races, we measured the amounts of salicylic acid (SA), the jasmonic acid-isoleucine conjugate (JA-Ile), other jasmonate precursors and derivatives, and abscisic acid (ABA) in four different species (Medicago sativa, Trifolium pratense, Pisum sativum, V. faba) after infestation by native and non-native pea aphid clones of various host races. Additionally, we assessed the performance of the clones on the four plant species. On M. sativa and T. pratense, non-native clones that were barely able to survive or reproduce, triggered a strong SA and JA-Ile response, whereas infestation with native clones led to lower levels of both phytohormones. On P. sativum, non-native clones, which survived or reproduced to a certain extent, induced fluctuating SA and JA-Ile levels, whereas the native clone triggered only a weak SA and JA-Ile response. On the universal host V. faba all aphid clones triggered only low SA levels initially, but induced clone-specific patterns of SA and JA-Ile later on. The levels of the active JA-Ile conjugate and of the other JA-pathway metabolites measured showed in many cases similar patterns, suggesting that the reduction in JA signaling was due to an effect upstream of OPDA. ABA levels were downregulated in all aphid clone-plant combinations and were therefore probably not decisive factors for aphid-plant compatibility. Our results suggest that A. pisum clones manipulate plant-defense signaling to their own advantage, and perform better on their native hosts due to their ability to modulate the SA- and JA-defense signaling pathways.